Port cities and landscapes of the sea. Issue 4 (2nd October 2022) - John-Alder, Kathleen; Whiteman, Stephen H.
Abstract: Ports and their oceanic hinterlands are distinctively malleable, permeable places. They are defined by morphologies that articulate shifting perspectives on the meanings of coastal settlements and their relationship to the term landscape. This essay introduces the co-editors' perspectives on port cities and the sea as distinctive modes of landscape, situating them, and the essays within the special issue, within a broader field of landscape studies.